The regulation of BK channel activity by pre- and post-translational modifications - Kyle, Barry D.; Braun, Andrew P. (Frontiers in Physiology, 2014)
Large conductance, Ca2+-activated K+ (BK) channels represent an important pathway for the outward flux of K+ ions from the intracellular compartment in response to membrane depolarization, and/or an elevation in cytosolic free [Ca2+]. They are functionally expressed in a range of mammalian tissues (e.g. nerve and smooth muscles), where they can either enhance or dampen membrane excitability. The diversity of BK channel activity results from the considerable alternative mRNA splicing and post-translational modification (e.g. phosphorylation) of key domains within the pore-forming alpha subunit of the channel complex. Most of these modifications are regulated by distinct upstream cell signaling pathways that influence the structure and/or gating properties of the holo-channel and ultimately, cellular function. The channel complex may also contain auxiliary subunits that further affect channel gating and behavior, often in a tissue-specific manner. Recent studies in human and animal models have provided strong evidence that abnormal BK channel expression/function contributes to a range of pathologies in nerve and smooth muscle. By targeting the upstream regulatory events modulating BK channel behavior, it may be possible to therapeutically intervene and alter BK channel expression/function in a beneficial manner.